Does Foraging or the Avoidance of Predation Determine Habitat Selection by Selective Resident Grazers in the Serengeti Woodlands? A Mixed Strategy with Season - Patrick Duncan; Anthony R. E. Sinclair (Animals)
Savanna systems are characterised by a community of large mammal herbivores with up to 30 species; coexistence is based on resource partitioning. In this paper we analyse the features of the landscape and plant structure which lead herbivores to use particular locations, a key to resource partitioning. The processes involved, top-down versus bottom-up, are well known for large species and small ones but not for medium-sized ones. We use two resident, medium-sized species, topi (Damaliscus lunatus jimela) and kongoni, (Alcelaphus buselaphus cokei) in the central woodlands of the Serengeti; selection of habitat by the residents is important for predator-prey interactions and for interactions among the grazers. Using Principal Component Analysis and Multiple Regression we develop highly predictive models which show that resource availability is the critical determinant of habitat selection in the dry season; and reduction in predation risk appears to be important in the wet season. These results show for the first time that habitat selection by the medium-sized herbivores is driven by different strategies in the two seasons. This contributes to understanding the processes involved in the dynamics of this globally important savanna system, a necessary foundation for management.